Caesarean delivery and risk of developing atopic diseases in children - Anak Agung Tri Yuliantini; Mohammad Juffrie; Ketut Dewi Kumara Wati (Indonesian Pediatric Society, 2014)
Background Caesarean delivery has been suggested to alterneonatal immune respon ses and increase the risk of atopicdiseases. Howevei; previous studies have reported inconsistentfindings.Objective To investigate a possible association between caesareandelivery and the development of atopic diseases in children.Methods This case-control study involved 100 children aged 3months-12 years, in Sanglah Hospital, Denpasai; Indonesia. Fiftyinfants and children with a confirmed diagnosis of atopic diseasesand 50 sex-paired controls (non-atopic infants and children)were enrolled. Demographic data was obtained, including modeof delivery and relevant history connected to atopic diseases.Skin prick test to four common aeroallergens was performed inall subjects. Possible confounding factors were considered in amultivariable logis tic regression model.Results Caesarean section was not significant as a risk factor foratopic diseases in a multivariate analysis [OR 2.4 (95%CI 0.7 to8.4; P=0.164)]. Howevei; multiple logistic regression analysisshowed that atopic diseases was significantly associated with apositive family history of atopy. Furthermore, caesarean sectionwas associated with a higher risk of atopic diseases in a subgroupanalysis for family history of atopy [OR= 4 (95%CI 1 to 16.2;P= 0.04)].Conclusion Children delivered by caesarean section and have afamily history of atopy have a 4-fo ld higher risk of atopic diseases.